Jornadas de auto y mutua capacitación con los maestros y las maestras de Lengua y Cultura del distrito de Chirripó - Hannia Watson-Soto; Lolita Camacho-Brown; Cristian Brenes-Granados (Universidad Nacional, Costa Rica, 2007)
The author presents the Project "Journeys of auto and mutual training in Chirripó District" that were developed with mother tongue and culture teachers in Cabécares communities to diminish the educative gaps that these communities have. The project brings a strategy to improve the quality of teaching practices and generates culturally pertinent educational processes.